Laminated battery cell
By providing a recess on the outermost side of the electrode sheet of the laminated battery, the problems of deterioration of lithium ion diffusion kinetics caused by the increase in the thickness of the electrode sheet and the easy fall off of the active coating, thereby improving the battery performance.
Patent Information
- Application Number
- CN202421460489.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-24
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2034-06-24
AI Technical Summary
During the manufacturing process of laminated batteries, the increase in the thickness of the electrode sheet leads to a deterioration of the diffusion kinetics of lithium ions, affecting the battery's magnification and cycling performance, and the active coating is prone to fall off, affecting the battery's performance.
By providing a recess on the outermost side of the electrode sheet, the maximum distance from the recess to the edge of the electrode sheet is between 0.5 mm and 20 mm, the cohesion of the active material layer and the adhesion to the foil are increased, and the active material layer is prevented from falling off.
Effectively prevent the active material layer on the outermost side of the electrode sheet from falling off, ensuring that the energy density of the battery is not lost, and ensuring excellent battery performance.
Smart Images

Figure CN222775327U_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and in particular to a laminated battery cell. Background Art
[0002] Lithium-ion batteries are widely used in mobile phones, laptops, electric vehicles and other fields. With the gradual expansion of application market demand, new requirements have been put forward for the energy density of lithium-ion batteries. Using thick pole pieces and increasing compaction density to obtain lithium-ion batteries with higher energy density is currently the most important and effective method. On the other hand, compared with traditional wound batteries, laminated batteries have lower internal resistance, better energy density, and more flexible size manufacturing. Therefore, combining thick pole pieces with laminated battery technology is an important development direction for high energy density batteries in the future.
[0003] However, as the thickness of the electrode increases, when it reaches a certain value, the lithium ion diffusion kinetics of the electrode will deteriorate, affecting the rate and cycle performance of the lithium-ion battery. The existing technology improves the kinetics of thick electrode sheets by using the technology of making holes or punching lines on the surface of the electrode sheets. In the manufacturing process of stacked batteries, the electrode sheets need to be cut into small pieces and then stacked. When the electrode sheets are evenly punched, if the position of the groove is close to the edge of the electrode sheet, the active coating at the edge of the electrode sheet is easy to fall off, seriously affecting the battery performance. Utility Model Content
[0004] Based on this, the present application provides a laminated battery cell to solve the problem in the related art that the active coating is easy to fall off, affecting the battery performance.
[0005] The present application provides a laminated battery cell, comprising a pole piece and a pole ear, wherein a plurality of pole pieces are stacked and arranged, wherein the pole piece comprises a current collector and an active material layer located on at least one side of the current collector surface, wherein the pole ear is electrically connected to the current collector and extends out of the edge of the pole piece, wherein the active material layer comprises a plurality of recesses, and at least one recess is arranged adjacent to the edge of the pole piece;
[0006] On the surface of the pole piece, along a direction perpendicular to the long axis of the recess, the maximum distance between the recess and the edge of the pole piece on the side adjacent to the recess is D, and D satisfies: 0.5mm≤D≤20mm.
[0007] In a possible implementation, D satisfies: 1 mm ≤ D ≤ 10 mm.
[0008] In a possible implementation, the recess includes a groove, and the angle between the long axis direction of the groove and the extension direction of the pole ear is in the range of 0°-90°.
[0009] In a possible implementation, the angle between the long axis direction of the groove and the extension direction of the pole ear is 0° or 90°.
[0010] In a possible implementation, the recess includes a first groove and a second groove, and an angle between a long axis direction of the first groove and a long axis direction of the second groove is in a range of 0°-90°;
[0011] At least one first groove is arranged adjacent to the edge of the pole piece. On the surface of the pole piece, along the direction perpendicular to the long axis of the first groove, the maximum distance between the first groove and the edge of the pole piece adjacent to the first groove is A, and A satisfies: 0.5mm≤A≤20mm;
[0012] At least one second groove is arranged adjacent to the edge of the pole piece. On the surface of the pole piece, along the direction perpendicular to the long axis of the second groove, the maximum distance between the second groove and the edge of the pole piece adjacent to the second groove is B, and B satisfies: 0.5mm≤B≤20mm.
[0013] In a possible implementation, A satisfies: 1 mm ≤ A ≤ 10 mm; and / or
[0014] B satisfies: 1mm≤B≤10mm.
[0015] In a possible implementation, an angle between a long axis direction of the first groove and a long axis direction of the second groove is 90°.
[0016] In a possible implementation, the plurality of recesses are distributed at equal intervals, or the plurality of recesses are distributed at unequal intervals.
[0017] In a possible implementation, the depth of the concave portion ranges from 4 μm to 30 μm; and / or
[0018] The width of the recess is in the range of 20 μm to 300 μm; and / or
[0019] The spacing between the recesses ranges from 0.3 mm to 5 mm.
[0020] In a possible implementation, the electrode sheet is a negative electrode sheet, the active material layer is a negative electrode active material layer, the surface density of the negative electrode active material layer is C1, the spacing between the concave portions is d1, and d1 satisfies: d1≥2 / (NC1); and / or
[0021] The electrode sheet is a positive electrode sheet, the active material layer is a positive electrode active material layer, the surface density of the positive electrode active material layer is C2, the spacing between the concave portions is d2, and d2 satisfies: d2≥10 / (3NC2),
[0022] Where N is a constant 10 g / cm 3 .
[0023] In a possible implementation, the electrode piece is a positive electrode piece, and the positive electrode piece further includes a ceramic layer, and the ceramic layer is arranged on the electrode ear and adjacent to the edge of the electrode piece.
[0024] In a possible implementation, in the extension direction of the pole ear, the orthographic projection of the ceramic layer coincides with the orthographic projection of the pole ear, and the width of the ceramic layer is smaller than the width of the pole ear extending from the edge of the pole piece.
[0025] In a possible implementation, the width of the ceramic layer along the extension direction of the pole ear is in the range of 0.1 μm to 3 μm.
[0026] In a possible implementation, at the edge of the pole piece where the pole lug is provided, the active material layer contains ceramic particles.
[0027] In the laminated battery provided by the present application, the maximum distance D between the outermost recess of the pole piece and the edge of the pole piece adjacent to the recess satisfies: 0.5mm≤D≤20mm. By setting the distance from the outermost recess of the pole piece to the edge of the pole piece, the cohesive force on the outermost active material layer of the pole piece and the peeling force of the foil can be increased, preventing the outermost active material layer of the pole piece from falling off, thereby ensuring that the energy density of the battery cell is not lost and the performance of the battery cell is ensured. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, a brief introduction will be given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0029] Figure 1 This is one of the schematic diagrams of the structure of the pole piece provided in the embodiment of the present application;
[0030] Figure 2 This is the second structural schematic diagram of the pole piece provided in the embodiment of the present application;
[0031] Figure 3 This is the third structural schematic diagram of the pole piece provided in the embodiment of the present application;
[0032] Figure 4 This is the fourth structural schematic diagram of the pole piece provided in the embodiment of the present application;
[0033] Figure 5 This is the fifth structural schematic diagram of the pole piece provided in the embodiment of the present application;
[0034] Figure 6 This is the sixth structural schematic diagram of the pole piece provided in the embodiment of the present application;
[0035] Figure 7 This is the seventh structural schematic diagram of the pole piece provided in the embodiment of the present application;
[0036] Figure 8 This is the eighth structural schematic diagram of the pole piece provided in the embodiment of the present application;
[0037] Fig. 9 This is a ninth structural diagram of a pole piece provided in an embodiment of the present application;
[0038] Fig.10 It is a schematic diagram of the structure of the laminated battery cell provided in the embodiment of the present application.
[0039] Description of reference numerals:
[0040] 100-pole sheet; 101-positive electrode sheet; 102-negative electrode sheet; 10-current collector; 11-positive current collector; 12-negative current collector; 20-active material layer; 21-positive active material layer; 22-negative active material layer; 23-second active material layer; 30-pole ear; 31-positive electrode ear; 32-negative electrode ear; 40-recess; 41-groove; 42-first groove; 43-second groove; 50-ceramic layer; 200-laminated battery cell; 201-diaphragm. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme in the embodiment of the present application will be described in more detail below in conjunction with the drawings in the preferred embodiments of the present application. In the drawings, the same or similar reference numerals throughout represent the same or similar parts or parts with the same or similar functions. The described embodiments are part of the embodiments of the present application, not all of the embodiments. The embodiments described below with reference to the drawings are exemplary and are intended to be used to explain the present application, and should not be construed as limitations on the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application. The embodiments of the present application are described in detail below in conjunction with the drawings.
[0042] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, or it can be an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0043] In the description of the present application, it should be understood that the terms "upper", "lower", "front", "back", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating orientations or positional relationships, are orientations or positional relationships based on the drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.
[0044] The terms "first", "second" and "third" (if any) in the specification and claims of this application and the above drawings are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence.
[0045] In addition, the terms "comprises," "comprising," and "having," and any variations thereof, are intended to cover a non-exclusive inclusion, for example, a process, method, system, product, or display comprising a series of steps or elements is not necessarily limited to those steps or elements explicitly listed, but may include other steps or elements not explicitly listed or inherent to such process, method, product, or display.
[0046] Lithium-ion batteries are widely used in mobile phones, laptops, electric vehicles and other fields. As the demand for application markets gradually expands, new requirements are also put forward for the energy density of lithium-ion batteries. The main means to improve the energy density of single cells are: (1) using positive and negative electrode materials with larger specific capacity; the specific capacity of commercial positive and negative electrode materials is close to the theoretical limit, and this method is temporarily ineffective before finding positive and negative electrode materials with larger specific capacity; (2) increasing the proportion of active materials in battery materials. The methods of using this method to improve energy density include using thinner diaphragms and current collectors, using thick pole pieces, and increasing compaction density. However, thinner diaphragms and current collectors have reached technical bottlenecks. Therefore, using thick pole pieces and increasing compaction density to obtain lithium-ion batteries with higher energy density is currently the most important and effective method. On the other hand, compared with traditional wound batteries, laminated batteries have lower internal resistance, better energy density, and more flexible size manufacturing. Therefore, combining thick pole pieces with laminated battery technology is an important development direction for high energy density batteries in the future.
[0047] However, as the thickness of the electrode increases, when it reaches a certain value, the lithium ion diffusion kinetics of the electrode will deteriorate, affecting the rate and cycle performance of the lithium-ion battery. The existing technology improves the kinetics of thick electrode sheets by using the technology of making holes or punching lines on the surface of the electrode sheets, among which the technology of forming grooves on the surface of the electrode sheets by laser punching has been applied. In the manufacturing process of stacked batteries, the electrode sheets need to be cut into small pieces and then stacked. When the electrode sheets are uniformly punched, the distance between the position of the groove formed by the laser punching and the edge of the electrode sheet cannot be controlled during the cutting process. If the position of the groove is close to the edge of the electrode sheet, a strip of active coating at the edge of the electrode sheet is easy to fall off, seriously affecting the battery performance.
[0048] After repeated thinking and verification, the inventor found that if the distance from the outermost groove of the pole piece to the edge of the pole piece is set to be greater than a certain distance. By setting the distance from the outermost groove of the pole piece to the edge of the pole piece to meet a certain width, the cohesive force of the active coating on the outermost side of the pole piece and the peeling force of the foil can be increased, preventing the outermost active material layer of the pole piece from falling off, thereby ensuring that the energy density of the battery is not lost and ensuring the performance of the battery.
[0049] In view of this, the present application provides a laminated battery cell, comprising a pole piece and a pole ear, wherein a plurality of pole pieces are stacked, the pole piece comprises a current collector and an active material layer located on at least one side of the current collector surface, the pole ear is electrically connected to the current collector and extends out of the edge of the pole piece, the active material layer comprises a plurality of recesses, and at least one recess is disposed adjacent to the edge of the pole piece;
[0050] On the surface of the pole piece, along a direction perpendicular to the long axis of the recess, the maximum distance between the recess and the edge of the pole piece on the side adjacent to the recess is D, and D satisfies: 0.5mm≤D≤20mm.
[0051] By setting the distance from the outermost recess of the pole piece to the edge of the pole piece, the cohesive force on the outermost active material layer of the pole piece and the peeling force with the foil can be increased, preventing the outermost active material layer of the pole piece from falling off, thereby ensuring that the energy density of the battery cell is not lost and ensuring the performance of the battery cell.
[0052] The contents of the present application will be described in detail below in conjunction with the accompanying drawings so that those skilled in the art can understand the contents of the present application more clearly and in detail.
[0053] Reference Figure 1-Figure 10 As shown, the pole piece 100 provided in the embodiment of the present application includes a current collector 10, an active material layer 20 and a pole tab 30. The active material layer 20 is located on at least one side of the surface of the current collector 10. The pole tab 30 is electrically connected to the current collector 10 and extends out of the edge of the pole piece 100.
[0054] In the embodiment of the present application, the electrode sheet 100 may be a positive electrode sheet 101 , wherein the current collector 10 is a positive electrode current collector 11 , the active material layer 20 is a positive electrode active material layer 21 , and the electrode tab 30 is a positive electrode tab 31 .
[0055] The electrode sheet 100 may also be a negative electrode sheet 102 , wherein the current collector 10 is a negative electrode current collector 12 , the active material layer 20 is a negative electrode active material layer 22 , and the electrode tab 30 is a negative electrode tab 32 .
[0056] The positive electrode sheet 101 and the negative electrode sheet 102 have opposite polarities.
[0057] In a possible implementation, the positive electrode sheet 101 uses aluminum foil as the positive electrode current collector 11 , and the negative electrode sheet 102 uses copper foil as the negative electrode current collector 12 .
[0058] The battery provided in this embodiment is a laminated battery core 200. The positive electrode sheet 101, the separator 201 and the negative electrode sheet 102 are cut to a certain width and then stacked in sequence.
[0059] The separator 201 is used to prevent a contact short circuit between the positive electrode sheet 101 and the negative electrode sheet 102 .
[0060] like Figure 1 As shown, the active material layer 20 includes a plurality of recesses 40 , and the recesses 40 are arranged at intervals.
[0061] Several means that there may be one, two, three or more. Therefore, several recesses 40 means that there may be one, two, three or more recesses 40.
[0062] Preferably, the electrode sheet 100 is a negative electrode sheet 102. Providing a recess 40 on the negative electrode sheet 102 can improve the flow of the electrolyte, enhance the wetting ability of the electrolyte on the electrode sheet, improve the negative electrode surface density and negative electrode dynamics, alleviate the negative electrode lithium deposition, and increase the liquid storage capacity.
[0063] The recess 40 may be provided on the active material layer 20 on one surface of the current collector 10 , or may be provided on the active material layer 20 on both surfaces of the current collector 10 .
[0064] The recess 40 includes a hole and / or a groove 41 . The hole is opened along the thickness direction of the pole piece 100 , and the groove 41 extends perpendicular to the thickness direction of the pole piece 100 , that is, the groove 41 extends in the plane where the active material layer 20 is located.
[0065] Preferably, the concave portion 40 is a groove 41 , which can be opened by a laser, and the grooves 41 can be opened continuously, thereby improving the flow of the electrolyte and enhancing the wetting ability of the electrolyte to the electrode 100 .
[0066] Preferably, the electrode sheet 100 is a negative electrode sheet 102, and the formation of the groove 41 can alleviate the lithium deposition in the negative electrode and increase the liquid storage capacity.
[0067] On the surface of the pole piece 100 , along a direction perpendicular to the long axis of the recess 40 , the maximum distance between the outermost recess 40 of the pole piece 100 and the edge of the pole piece 100 adjacent to the recess 40 is D, and D satisfies: 0.5mm≤D≤20mm.
[0068] Preferably, D satisfies: 1mm≤D≤10mm.
[0069] In a possible implementation, the angle between the long axis direction of the groove 41 and the extension direction of the pole tab 30 is in the range of 0°-90°.
[0070] like Figure 1 As shown, the extension direction of the pole tab 30 is X. The recess 40 is a groove 41 , and the long axis direction of the groove 41 is perpendicular to the extension direction of the pole tab 30 , that is, the angle is 90°.
[0071] like Figure 2 As shown, the long axis direction of the groove 41 is parallel to the extension direction of the pole ear 30, that is, the included angle is 0°.
[0072] like Figure 3 As shown, the angle between the long axis direction of the groove 41 and the extending direction of the pole ear 30 is 45°.
[0073] like Figures 1 to 3 As shown, there are spaces between the plurality of recesses 40 .
[0074] In a possible implementation, the electrode sheet 100 is a negative electrode sheet 102 , the surface density of the negative electrode active material layer 22 is C1 (g / cm 2 ), the spacing between the recesses 40 is d1 (mm), and d1 satisfies: d1 ≥ 2 / (NC1).
[0075] In a possible implementation, the electrode sheet 100 is a positive electrode sheet 101, the surface density of the positive electrode active material layer 21 is C2 (g / cm2), the spacing between the recesses 40 is d2 (mm), and d2 satisfies: d2≥10 / (3NC2).
[0076] Where N is a constant 10 g / cm 3 .
[0077] In a possible implementation, a plurality of recesses 40 are distributed at equal intervals.
[0078] In another possible implementation, the plurality of recesses 40 are distributed at unequal intervals.
[0079] In a possible implementation, the depth of the recess 40 ranges from 4 μm to 30 μm.
[0080] In a possible implementation, the width of the recess 40 ranges from 50 μm to 300 μm.
[0081] In a possible implementation, the interval between the recesses 40 ranges from 0.3 mm to 5 mm.
[0082] like Figures 4 to 6 As shown, in a possible implementation, the recess 40 includes a first groove 42 and a second groove 43 .
[0083] The first groove 42 and the second groove 43 extend in different directions, that is, the first groove 42 and the second groove 43 intersect each other, or the extension lines of the first groove 42 and the second groove 43 intersect each other.
[0084] By providing two groups of mutually intersecting first grooves 42 and second grooves 43, the area of the pole piece 100 without grooves can be reduced, thereby reducing the influence of the area without grooves on the rate and cycle performance of the battery.
[0085] The first groove 42 and the second groove 43 respectively include a plurality of grooves arranged at intervals.
[0086] The distance between the first grooves 42 is a, and the distance between the second grooves 43 is b.
[0087] In a possible implementation, the electrode sheet 100 is a negative electrode sheet 102, the active material layer is a negative electrode active material layer 22, the surface density of the negative electrode active material layer 22 is C1 (g / cm2), and a and b satisfy: a≥2 / (NC1); b≥2 / (NC1).
[0088] In a possible implementation, the electrode sheet 100 is a positive electrode sheet 101, the active material layer is a positive electrode active material layer 21, the surface density of the positive electrode active material layer 21 is C2 (g / cm2), and a and b satisfy: a≥10 / (3NC2); b≥10 / (3NC2).
[0089] Where N is a constant 10 g / cm 3 .
[0090] On the surface of the pole piece 100 , along a direction perpendicular to the long axis of the first groove 42 , the maximum distance between the outermost first groove 42 of the pole piece 100 and the edge of the pole piece 100 adjacent to the first groove 42 is A, and A satisfies: 0.5mm≤A≤20mm.
[0091] Preferably, A satisfies: 1mm≤A≤10mm.
[0092] On the surface of the pole piece 100 , along a direction perpendicular to the long axis of the second groove 43 , the maximum distance between the outermost second groove 43 of the pole piece 100 and the edge of the pole piece 100 adjacent to the second groove 43 is B, and B satisfies: 0.5mm≤B≤20mm.
[0093] Preferably, B satisfies: 1mm≤B≤10mm.
[0094] In a possible implementation, a plurality of first grooves 42 and second grooves 43 are distributed at equal intervals.
[0095] In another possible implementation, the plurality of first grooves 42 are distributed at unequal intervals, and / or the plurality of second grooves 43 are distributed at unequal intervals.
[0096] In a possible implementation, the angle between the long axis direction of the first groove 42 and the long axis direction of the second groove 43 is in the range of 0°-90°.
[0097] Preferably, the angle between the long axis direction of the first groove 42 and the long axis direction of the second groove 43 is 90°, that is, the long axis direction of the first groove 42 and the long axis direction of the second groove 43 are perpendicular to each other.
[0098] like Figure 4 As shown, the long axis direction of the first groove 42 is parallel to the extension direction of the pole lug 30, that is, the angle is 0°, and the long axis direction of the second groove 43 is perpendicular to the extension direction of the pole lug 30, that is, the angle is 90°.
[0099] like Figure 5 As shown, the long axis direction of the first groove 42 is perpendicular to the extension direction of the pole lug 30, that is, the angle is 90°, and the long axis direction of the second groove 43 is parallel to the extension direction of the pole lug 30, that is, the angle is 0°.
[0100] like Figure 6 As shown, the angle between the long axis direction of the first groove 42 and the extension direction of the pole tab 30 is 45°, the angle between the long axis direction of the second groove 43 and the extension direction of the pole tab 30 is 45°, and the long axis direction of the first groove 42 and the long axis direction of the second groove 43 are perpendicular to each other.
[0101] It can be understood that in another possible implementation, the recess 40 further includes a plurality of holes and / or grooves extending in different directions.
[0102] In a possible implementation, the electrode sheet 100 is a positive electrode sheet 101 , and the positive electrode sheet 101 includes a positive electrode current collector 11 , a positive electrode active material layer 21 and a positive electrode tab 31 .
[0103] Specifically, the positive electrode active material layer 21 includes a positive electrode active material, a conductive agent, and a binder.
[0104] In one possible implementation, the positive electrode active material includes at least one of lithium cobalt oxide (LCO), nickel cobalt manganese ternary material (NCM), nickel cobalt aluminum ternary material (NCA), nickel cobalt manganese aluminum quaternary material (NCMA), lithium iron phosphate (LFP), lithium manganese phosphate (LMP), lithium vanadium phosphate (LVP), lithium manganese oxide (LMO), and lithium-rich manganese-based.
[0105] In a possible implementation, the conductive agent includes at least one of conductive carbon black, carbon nanotubes, conductive graphite, and graphene.
[0106] In one possible implementation, the adhesive includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, polyhexafluoropropylene and styrene-butadiene rubber.
[0107] like Figure 7 As shown, in a possible implementation, the positive electrode sheet 101 further includes a ceramic layer 50 , and the ceramic layer 50 is disposed on the positive electrode ear 31 and adjacent to the edge of the positive electrode sheet 101 .
[0108] In the extension direction of the positive electrode tab 31 , the orthographic projection of the ceramic layer 50 coincides with the orthographic projection of the positive electrode tab 31 , and the width of the ceramic layer 50 is smaller than the width of the positive electrode tab 31 extending from the edge of the electrode sheet 100 .
[0109] Disposing a ceramic layer 50 at the edge of the positive ear 31 near the positive electrode sheet 101 is beneficial to improving the transmission of lithium ions between the positive and negative electrode sheets. At the same time, the ceramic layer 50 can also prevent the powder in the groove 41 on the negative electrode sheet 102 from falling into the positive electrode active material layer 21 and the positive ear 31 area, causing a short circuit.
[0110] In a possible implementation, the width of the ceramic layer 50 along the extension direction of the positive electrode tab 31 ranges from 0.1 μm to 3 μm.
[0111] Specifically, the ceramic layer 50 is used to prevent the powder in the groove 41 on the negative electrode sheet 102 from falling, and to prevent the heat on the electrode sheet from being transferred to the electrode tab 30, causing heat accumulation at the electrode tab 30. If the width of the ceramic layer 50 is less than 0.1 μm, it cannot prevent the powder from falling and prevent heat accumulation. If it exceeds 3 μm, it will reduce the electrical conductivity, increase polarization, and reduce the rate performance of the battery. Therefore, the width of the ceramic layer 50 ranges from 0.1 μm to 3 μm.
[0112] Specifically, the ceramic layer 50 includes ceramic particles.
[0113] In a possible implementation, the ceramic layer 50 includes at least one of ceramic particles such as aluminum oxide, quartz, magnesium oxide, and titanium oxide.
[0114] like Figure 8 As shown, in a possible implementation, at the edge of the pole piece 100 where the pole ear 30 is provided, the active material layer 20 also includes ceramic particles, that is, at the edge of the pole piece 100 where the pole ear 30 is provided, the active material layer 20 is a second active material layer 23, and the second active material layer 23 includes positive electrode active material, conductive agent, adhesive and ceramic particles.
[0115] In a possible implementation, at the edge of the pole piece 100 where the pole tab 30 is not provided, the active material layer 20 does not contain ceramic particles.
[0116] The edges where the pole tabs 30 are not provided do not contain ceramic particles, which can increase the utilization space of the active layer, thereby increasing the energy density and helping to improve the problem of lithium deposition at the edges.
[0117] In a possible implementation, the electrode sheet 100 is a negative electrode sheet 102 , and the negative electrode sheet 102 includes a negative electrode current collector 12 , a negative electrode active material layer 22 and a negative electrode ear 32 .
[0118] Specifically, the negative electrode active material layer 22 includes a negative electrode active material, a conductive agent, and a binder.
[0119] In a possible implementation, the negative electrode active material includes at least one of graphite, mesophase carbon microbeads, soft carbon, hard carbon, silicon material, silicon-oxygen material, silicon-carbon material, and lithium titanate.
[0120] In a possible implementation, the conductive agent includes at least one of conductive carbon black, carbon nanotubes, conductive graphite, and graphene.
[0121] In one possible implementation, the adhesive includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, polyhexafluoropropylene and styrene-butadiene rubber.
[0122] like Fig. 9 As shown, in a possible implementation, the groove 41 may also be a curved groove, in which the maximum distance between the outermost groove 41 and the edge of the pole piece 100 adjacent to the groove 41 is D, and D satisfies: 0.5mm≤D≤20mm.
[0123] Preferably, D satisfies: 1mm≤D≤10mm.
[0124] The pole piece 100 provided in the embodiment of the present application includes a current collector 10 and an active material layer 20 located on at least one side of the surface of the current collector 10, the pole ear 30 is electrically connected to the current collector 10 and extends out of the edge of the pole piece 100, the active material layer 20 contains a plurality of recesses 40, and at least one recess 40 is arranged adjacent to the edge of the pole piece; on the surface of the pole piece 100, along a direction perpendicular to the long axis of the recess 40, the maximum distance between the recess 40 and the edge of the pole piece 100 on the side adjacent to the recess 40 is D, and D satisfies: 0.5mm≤D≤20mm.
[0125] By setting the distance from the outermost recess 40 of the pole piece 100 to the edge of the pole piece 100, the cohesive force exerted on the outermost active material layer 20 of the pole piece 100 and the peeling force of the bonding with the foil can be increased, preventing the outermost active material layer 20 of the pole piece 100 from falling off, thereby ensuring that the energy density of the battery is not lost and ensuring the performance of the battery.
[0126] In addition, if Fig.10 As shown, the embodiment of the present application further provides a laminated battery core 200, comprising a plurality of the above-mentioned pole pieces 100, wherein the plurality of pole pieces 100 are stacked.
[0127] The laminated battery is not limited to lithium batteries, and in the future this technology may be applied to sodium batteries, etc. The embodiment of the present application preferably uses lithium-ion batteries.
[0128] The electrode sheet 100 includes a positive electrode sheet 101 and a negative electrode sheet 102 , and the laminated battery cell 200 also includes a separator 201 .
[0129] The positive electrode sheet 101 , the separator 201 and the negative electrode sheet 102 are cut to a certain width and then stacked in sequence in the housing.
[0130] The separator 201 is used to prevent a contact short circuit between the positive electrode sheet 101 and the negative electrode sheet 102 .
[0131] The specific structure, working principle and function of the electrode 100 have been described in detail in the above embodiments and will not be repeated here. It should be noted that the preparation process of the lithium-ion battery is as follows:
[0132] Example 1
[0133] Step 1, preparation of positive electrode sheet 101: disperse the positive electrode active material lithium cobalt oxide, binder PVDF and conductive carbon black in N-methylpyrrolidone to obtain a uniform positive electrode active material slurry; in the positive electrode active material layer slurry, the solid components include 97wt% lithium cobalt oxide, 2wt% binder PVDF and 1wt% conductive agent. Use a coating machine to coat the active material layer, which includes a coated area and an uncoated area in the width direction of the coating. After drying, rolling, slitting and die-cutting, small positive electrode sheets of a certain size and shape are obtained.
[0134] Step 2, preparation of negative electrode sheet 102: graphite, binder styrene butadiene rubber, thickener sodium carboxymethyl cellulose and conductive agent conductive carbon black are mixed and dispersed in deionized water to obtain negative electrode slurry; in the negative electrode slurry, the solid components include 97wt% graphite, 1.5wt% sodium carboxymethyl cellulose, 0.5wt% conductive carbon black, and 1wt% styrene butadiene rubber. The solid content in the negative electrode slurry is 40-45wt%; the negative electrode slurry is evenly coated on both sides of the copper foil, and the coating width direction includes a coated area and an uncoated area. After drying and rolling, the rolled negative electrode sheet is obtained, and the rolled negative electrode sheet is thinned by laser or other physical and mechanical methods to obtain a groove 41 on the negative electrode sheet, and the spacing distance d1 of the groove 41 is 1mm. Finally, the negative electrode sheet is cut and die-cut to obtain a small negative electrode sheet. During the die-cutting process, ensure that the distance D between the edge groove 41 of the negative electrode sheet and the edge of the negative electrode sheet is equal to 3mm.
[0135] Step 3: Prepare lithium-ion batteries: stack the prepared positive electrode sheets, separators and negative electrode sheets in sequence to obtain laminated cells. Use aluminum-plastic film packaging, bake for 24 hours in a vacuum state to remove moisture, inject electrolyte, and then form, vacuum seal and sort the battery to obtain a soft-pack lithium-ion battery.
[0136] The electrolyte is a commercially available conventional electrolyte, and the lithium salt therein is LiFP6.
[0137] Example 2
[0138] Preparation of positive electrode sheet 101: The positive electrode sheet is dried and rolled to obtain a rolled positive electrode sheet, and the rolled positive electrode sheet is thinned by laser or other physical and mechanical methods to obtain grooves 41 on the positive electrode sheet, and the spacing distance d2 of the grooves 41 is 1 mm. Finally, the positive electrode sheet is cut and die-cut to obtain small positive electrode sheets. During the die-cutting process, it is ensured that the distance D between the groove 41 at the edge of the positive electrode sheet and the edge of the positive electrode sheet is equal to 3 mm. Others are the same as in Example 1.
[0139] Example 3
[0140] Preparation of negative electrode sheet 102: Graphite, binder styrene butadiene rubber, thickener sodium carboxymethyl cellulose and conductive agent conductive carbon black are mixed and dispersed in deionized water to obtain negative electrode slurry; in the negative electrode slurry, the solid components include 97wt% graphite, 1.5wt% sodium carboxymethyl cellulose, 0.5wt% conductive carbon black, and 1wt% styrene butadiene rubber. The solid content in the negative electrode slurry is 40-45wt%; the negative electrode slurry is evenly coated on both sides of the copper foil. After drying, rolling, slitting and die-cutting, negative electrode small sheets of a certain size and shape are obtained. Others are the same as in Example 2.
[0141] Example 4
[0142] Preparation of negative electrode sheet 102: Graphite, binder styrene butadiene rubber, thickener sodium carboxymethyl cellulose and conductive agent conductive carbon black are mixed and dispersed in deionized water to obtain negative electrode slurry; in the negative electrode slurry, the solid components include 97wt% graphite, 1.5wt% sodium carboxymethyl cellulose, 0.5wt% conductive carbon black, and 1wt% styrene butadiene rubber. The solid content in the negative electrode slurry is 40-45wt%; the negative electrode slurry is evenly coated on both sides of the copper foil, and the coating width direction includes a coated area and an uncoated area. After drying and rolling, a rolled negative electrode sheet is obtained, and the rolled negative electrode sheet is thinned by laser or other physical and mechanical methods to obtain a first groove 42 and a second groove 43 on the negative electrode sheet, and the spacing a of the first groove 42 and the spacing b of the second groove 43 are both 1mm. Finally, the negative electrode sheet is cut and die-cut to obtain a small negative electrode sheet. During the die-cutting process, ensure that the distances A and B between the first groove 42 and the second groove 43 at the edge of the negative electrode sheet and the edge of the negative electrode sheet are equal to 1.5 mm.
[0143] Example 5
[0144] Preparation of positive electrode sheet 101: The positive electrode sheet is dried and rolled to obtain a rolled positive electrode sheet, and the rolled positive electrode sheet is thinned by laser or other physical and mechanical methods to obtain a first groove 42 and a second groove 43 on the positive electrode sheet. The spacing a of the first groove 42 and the spacing b of the second groove 43 are both 1 mm. Finally, the positive electrode sheet is cut and die-cut to obtain small positive electrode sheets. During the die-cutting process, ensure that the distances A and B between the first groove 42 and the second groove 43 at the edge of the positive electrode sheet are equal to 1.5 mm. Others are the same as in Example 4.
[0145] Example 6
[0146] Preparation of negative electrode sheet 102: Graphite, binder styrene butadiene rubber, thickener sodium carboxymethyl cellulose and conductive agent conductive carbon black are mixed and dispersed in deionized water to obtain negative electrode slurry; in the negative electrode slurry, the solid components include 97wt% graphite, 1.5wt% sodium carboxymethyl cellulose, 0.5wt% conductive carbon black, and 1wt% styrene butadiene rubber. The solid content in the negative electrode slurry is 40-45wt%; the negative electrode slurry is evenly coated on both sides of the copper foil. After drying, rolling, slitting and die-cutting, negative electrode small sheets of a certain size and shape are obtained. Others are the same as in Example 5.
[0147] Example 7
[0148] Preparation of negative electrode sheet 102: Graphite, binder styrene butadiene rubber, thickener sodium carboxymethyl cellulose and conductive agent conductive carbon black are mixed and dispersed in deionized water to obtain negative electrode slurry; in the negative electrode slurry, the solid components include 97wt% graphite, 1.5wt% sodium carboxymethyl cellulose, 0.5wt% conductive carbon black, and 1wt% styrene butadiene rubber. The solid content in the negative electrode slurry is 40-45wt%; the negative electrode slurry is evenly coated on both sides of the copper foil, and the coating width direction includes a coated area and an uncoated area. After drying and rolling, the rolled negative electrode sheet is obtained, and the rolled negative electrode sheet is thinned by laser or other physical and mechanical methods to obtain a groove 41 on the negative electrode sheet, and the spacing distance d1 of the groove 41 is 1mm. Finally, the negative electrode sheet is cut and die-cut to obtain a small negative electrode sheet. During the die-cutting process, ensure that the distance D between the edge groove 41 of the negative electrode sheet and the edge of the negative electrode sheet is equal to 1mm. Others are the same as in Example 1.
[0149] Example 8
[0150] Preparation of negative electrode sheet 102: Graphite, binder styrene butadiene rubber, thickener sodium carboxymethyl cellulose and conductive agent conductive carbon black are mixed and dispersed in deionized water to obtain negative electrode slurry; in the negative electrode slurry, the solid components include 97wt% graphite, 1.5wt% sodium carboxymethyl cellulose, 0.5wt% conductive carbon black, and 1wt% styrene butadiene rubber. The solid content in the negative electrode slurry is 40-45wt%; the negative electrode slurry is evenly coated on both sides of the copper foil, and the coating width direction includes a coated area and an uncoated area. After drying and rolling, the rolled negative electrode sheet is obtained, and the rolled negative electrode sheet is thinned by laser or other physical and mechanical methods to obtain a groove 41 on the negative electrode sheet, and the spacing distance d1 of the groove 41 is 1mm. Finally, the negative electrode sheet is cut and die-cut to obtain a small negative electrode sheet. During the die-cutting process, ensure that the distance D between the edge groove 41 of the negative electrode sheet and the edge of the negative electrode sheet is equal to 10mm. Others are the same as in Example 1.
[0151] Comparative Example 1
[0152] There is no concave part in the positive and negative electrode sheets after rolling, that is, they are not processed by laser or other physical mechanical methods, and they are directly cut and die-cut to obtain positive electrode sheets and negative electrode sheets of a certain size and shape.
[0153] Comparative Example 2
[0154] During the preparation of the negative electrode sheet, die cutting is performed to ensure that the maximum distance D between the first groove 42 and the second groove 43 at the edge of the negative electrode sheet and the edge of the negative electrode sheet is equal to 0.4 mm. Other details are the same as those in Example 1.
[0155] Comparative Example 3
[0156] During the preparation of the negative electrode sheet, die cutting is performed to ensure that the distances A and B between the groove at the edge of the negative electrode sheet and the edge of the negative electrode sheet are equal to 0.4 mm.
[0157] Comparative Example 4
[0158] During the preparation of the negative electrode sheet, die cutting is performed to ensure that the maximum distance D between the edge groove 41 of the negative electrode sheet and the edge of the negative electrode sheet is equal to 25 mm.
[0159] It should be noted that the following is a table comparing the data of the dropout test, cycle life and capacity retention rate of the batteries prepared in each embodiment and the comparative example.
[0160] Table 1 is a data table of various examples and comparative examples
[0161]
[0162]
[0163] Among them, the statistical method for the shedding ratio of the edge active coating is:
[0164] 10,000 die-cut small pole pieces were taken, and a CCD microscope was used to observe and count the number of small pole pieces n whose active coatings fell off at the edge of the pole pieces. The shedding ratio P was calculated using the formula P=n / 10,000.
[0165] The test method for cycle life is:
[0166] Place the battery in a (25±3)℃ environment and let it stand for 3 hours. When the battery cell reaches (25±3)℃, charge the battery to 4.25V at 2C, then charge it to 4.48V at 0.7C, then charge it to a cutoff current of 0.05C at 4.48V, and then discharge it to 3V at 1C, and record the initial capacity Q0. When the cycle reaches the required number of times or the capacity attenuation rate is less than 70%, take the previous discharge capacity as the battery capacity Q2, and calculate the capacity retention rate (%):
[0167] Capacity retention rate (%) = Q2 / Q0×100%.
[0168] As shown in Table 1, the comparison between Comparative Example 1 and the embodiment shows that the use of laser wire-punching or other physical and mechanical methods to form a recess on the surface of the pole piece 100 can significantly improve the cycle life and capacity retention rate of the battery; the comparison between Comparative Examples 2 and 3 and the embodiment shows that when the distance between the outermost recess 40 of the pole piece 100 and the edge of the pole piece 100 is greater than 0.5 mm, the proportion of the outermost active material layer 20 falling off is significantly reduced; the comparison between Comparative Example 4 and the embodiment shows that when the distance between the outermost recess 40 of the pole piece 100 and the edge of the pole piece 100 is greater than 20 mm, the battery The cycle life is significantly reduced; the comparison between Example 4 and Example 1, the comparison between Example 5 and Example 2, and the comparison between Example 6 and Example 3 show that the battery capacity retention rate can be improved by providing two sets of mutually intersecting first grooves 42 and second grooves 43 on the electrode sheet 100; the comparison between Example 2 and Example 1 shows that the battery capacity retention rate can be improved by providing recesses on both the positive electrode sheet 101 and the negative electrode sheet 102; the comparison between Example 3 and Example 1 shows that providing a recess on the negative electrode sheet 102 can improve the battery capacity retention rate compared with providing a recess on the positive electrode sheet 101.
[0169] The stacked battery cell 200 provided in the embodiment of the present application can increase the cohesive force exerted on the outermost active material layer 20 of the electrode piece 100 and the peeling force of bonding with the foil material by setting the distance from the outermost recess 40 of the electrode piece 100 to the edge of the electrode piece 100, thereby preventing the outermost active material layer 20 of the electrode piece 100 from falling off, thereby ensuring that the energy density of the battery cell is not lost and ensuring the excellent rate performance of the battery cell.
[0170] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A laminated battery cell, characterized in that: The invention comprises a pole piece and a pole ear, wherein a plurality of the pole pieces are stacked and arranged, wherein the pole piece comprises a current collector and an active material layer located on at least one side of the current collector surface, wherein the pole ear is electrically connected to the current collector and extends out of the edge of the pole piece, wherein the active material layer comprises a plurality of recesses, and at least one of the recesses is arranged adjacent to the edge of the pole piece; On the surface of the pole piece, along a direction perpendicular to the long axis of the recess, the maximum distance between the recess and the edge of the pole piece on the side adjacent to the recess is D, and D satisfies: 0.5mm≤D≤20mm.
2. The laminated battery cell according to claim 1, characterized in that: D satisfies: 1mm≤D≤10mm.
3. The laminated battery cell according to claim 1, characterized in that: The recess comprises a groove, The angle between the long axis direction of the groove and the extension direction of the pole ear is in the range of 0°-90°.
4. The laminated battery cell according to claim 3, characterized in that: The angle between the long axis direction of the groove and the extension direction of the pole ear is 0° or 90°.
5. The laminated battery cell according to claim 1, characterized in that: The concave portion includes a first groove and a second groove, and the angle between the long axis direction of the first groove and the long axis direction of the second groove is in the range of 0°-90°; At least one of the first grooves is arranged adjacent to the edge of the pole piece. On the surface of the pole piece, along a direction perpendicular to the long axis of the first groove, the maximum distance between the first groove and the edge of the pole piece adjacent to the first groove is A, and A satisfies: 0.5 mm ≤ A ≤ 20 mm; At least one of the second grooves is arranged adjacent to the edge of the pole piece. On the surface of the pole piece, along the direction perpendicular to the long axis of the second groove, the maximum distance between the second groove and the edge of the pole piece adjacent to the second groove is B, and B satisfies: 0.5mm≤B≤20mm.
6. The laminated battery cell according to claim 5, characterized in that: A satisfies: 1mm≤A≤10mm; and / or B satisfies: 1mm≤B≤10mm.
7. The laminated battery cell according to claim 5, characterized in that: The angle between the long axis direction of the first groove and the long axis direction of the second groove is 90°.
8. The laminated battery cell according to any one of claims 1 to 7, characterized in that: The plurality of recesses are distributed at equal intervals, or the plurality of recesses are distributed at unequal intervals.
9. The laminated battery cell according to any one of claims 1 to 7, characterized in that: The depth of the recess is in the range of 4 μm to 30 μm; and / or The width of the concave portion is in the range of 20 μm to 300 μm; and / or The spacing between the recesses ranges from 0.3 mm to 5 mm.
10. The laminated battery cell according to claim 1, characterized in that: The electrode sheet is a negative electrode sheet, the active material layer is a negative electrode active material layer, the surface density of the negative electrode active material layer is C1, the spacing between the concave portions is d1, and d1 satisfies: d1≥2 / (NC1); and / or The electrode sheet is a positive electrode sheet, the active material layer is a positive electrode active material layer, the surface density of the positive electrode active material layer is C2, the spacing between the concave portions is d2, and d2 satisfies: d2≥10 / (3NC2), Where N is a constant 10 g / cm 3 .
11. The laminated battery cell according to claim 1, characterized in that: The pole piece is a positive pole piece, and the positive pole piece further comprises a ceramic layer, and the ceramic layer is arranged on the pole ear and adjacent to the edge of the pole piece.
12. The laminated battery cell according to claim 11, characterized in that: In the extension direction of the pole ear, the orthographic projection of the ceramic layer coincides with the orthographic projection of the pole ear, and the width of the ceramic layer is smaller than the width of the pole ear extending from the edge of the pole piece.
13. The laminated battery cell according to claim 11, characterized in that: The width of the ceramic layer along the extension direction of the electrode tab is in the range of 0.1 μm to 3 μm.
14. The laminated battery cell according to claim 1, characterized in that: At the edge of the pole piece where the pole ear is provided, the active material layer contains ceramic particles.
Citation Information
Cited By
Coating method of lithium ion battery pole piece and prepared lithium ion battery pole piece
CN120914207A